Complex trait divergence contributes to environmental niche differentiation in ecological speciation of Boechera stricta. Issue 8 (22nd February 2013) - Lee, Cheng‐Ruei; Mitchell‐Olds, Thomas
Abstract Ecological factors may contribute to reproductive isolation if differential local adaptation causes immigrant or hybrid fitness reduction. Because local adaptation results from the interaction between natural selection and adaptive traits, it is crucial to investigate both to understand ecological speciation. Previously, we used niche modelling to identify local water availability as an environmental correlate of incipient ecological speciation between two subspecies in Boechera stricta, a close relative of Arabidopsis. Here, we performed several large‐scale glasshouse experiments to investigate the divergence of various physiological, phenological and morphological traits. Although we found no significant difference in physiological traits, the Western subspecies has significantly faster growth rate, larger leaf area, less succulent leaves, delayed reproductive time and longer flowering duration. These trait differences are concordant with previous results that habitats of the Western genotypes have more consistent water availability, while Eastern genotypes inhabit locations with more ephemeral water supplies. In addition, by comparing univariate and multivariate divergence of complex traits (QST) to the genomewide distribution of SNP FST, we conclude that the aspects of phenology and morphology (but not physiology) are under divergent selection. In addition, we also identified several highly diverged traits without obvious water‐related functions.